The effect of modified medium on the growth of Begonia imperialis and Begonia ‘Bethlehem Star’ - DYAN MEININGSASI SISWOYO PUTRI (Biodiversitas Journal of Biological Diversity, 2006)
The aim of the research was to know the effect of modified medium on the growth of Begonia imperialis and Begonia ‘Bethlehem Star’. The design of the research used was Experimental by Factorial Cluster Random Sampling, by using types of media (I=soil (control); II=soil:sand:compost; III=soil:sand:’kompenit’; IV=soil:sand:humus V=soil:sand:manure) and the material (B. imperialis and B. ‘Bethlehem Star’). Sampling time (three replicated) was chosen in-groups. Observed parameters were plants tall, root, the numbers of shoots and the environmental factors (temperature and humidity). Analysist of variant showed that ‘kompenit’ is the best medium to support on the propagation of B. imperialis and B. ‘Bethlehem Star’.© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Begonia imperialis, Begonia ‘Bethlehem Star’, media, growth.